Analysis Of Reading Interest Through Picture Storybooks In Grade Iii Students At SDN Pangrango - Isnaeni Nur Azizah; Anggita Maharani (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Reading ability is a fundamental skill that plays a crucial role in supportingthe teaching and learning process. However, reading interest amongelementary school students—particularly at SDN Pangrango—remainssuboptimal. This study aims to analyze the reading interest of Grade IIIstudents at SDN Pangrango by utilizing picture storybooks as a medium. Thestudy employed a descriptive methodology with a qualitative approach. Theresearch participants consisted of 20 third-grade students. Data werecollected through direct observation and interviews, using instruments suchas questionnaires, interviews, and activity documentation. The analysisprocess included data reduction, information presentation, and drawingconclusions. The research findings indicate that the reading interest of GradeIII students is relatively good. This is evident from several indicators:students' enjoyment when reading picture storybooks, their interest in thestory content and illustrations, enthusiasm in using picture storybooks duringlessons, as well as their ability to comprehend and recall story content.Nevertheless, the habit of reading during free time still requiresimprovement.